Penguatan Pendidikan Karakter Melalui Konseling Kognitif Behavior Dalam Meningkatkan Belajar Bermakna - Khoerunnisa, Eka Yulia; Atmaja, Jati Rinakri (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2026)
This study aims to examine the effectiveness of strengthening character education through the Cognitive Behavior Therapy (CBT) approach in enhancing students’ meaningful learning. A quantitative method with a quasi-experimental one-group pretest–posttest design was employed. The participants were 30 students selected purposively based on low to moderate levels of meaningful learning. The instrument used was a Likert-scale Meaningful Learning Scale that had been tested for validity and reliability. Data were analyzed using a paired sample t-test to compare scores before and after the intervention. The findings revealed a significant increase in the mean score from 179.70 (pretest) to 199.30 (posttest), with a difference of 19.60 points. The calculated t-value of 10.944 (p < 0.001) indicates that the character-based CBT intervention is effective in improving meaningful learning. Additionally, the reduction in standard deviation from 13.49 to 11.59 suggests relatively homogeneous improvement among participants. Analytically, these results confirm that integrating cognitive restructuring, behavioral activation, and character value reinforcement enhances the internalization of learning. Theoretically, this study contributes an integrative CBT-character model linking cognitive, affective, and moral dimensions. Practically, it offers an evidence-based framework for implementing counseling services in higher education to improve student learning outcomes holistically. Keywords:cognitive behavior counseling, character education, meaningful learning